Synergity of religion, culture and arts: meeting point model of religious education for ustadz, culturals and artists in Garut district - Syahidin, S.; Parhan, Muhamad; Nugraha, Risris Hari (Universitas Pendidikan Indonesia, 2023)
Garut Regency is a religious area with good Human Resources (HR) potential, including many religious instructors, religious teachers, cultural figures, and artists. They became community figures who were influential enough to move the wheels of development in Garut society with a spiritual, arts, and cultural approach. However, their current existence has not been able to motivate people to improve their quality of life. The root of the problem is misperceptions among community leaders, especially religious counselors, religious teachers, artists, and cultural figures. They view that religious education or Islamic da'wah and the development of arts and culture are two different things and even tend to be contradictory. A qualitative research approach using descriptive analysis methods from field studies by synergizing and discussing with religious, arts, and cultural figures, then conducting workshops, preparing and disseminating model drafts in the form of limited training as a trial of the cultural approach to religious education model for religious instructors, Ustadz, Artists and Cultural People in Garut Regency. This activity aims to equalize perceptions about Islam and arts and culture and to create good synergy between religion, arts, and culture. This community service produces new ideas and models of religious education with an arts and culture approach that elevates and socializes local wisdom.